2010
DOI: 10.1177/0961203309355301
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of asymptomatic hyperuricaemia and serum uric acid levels with arterial stiffness in women with systemic lupus erythematosus without clinically evident atherosclerotic cardiovascular disease

Abstract: The objective of this article was to evaluate whether serum uric acid (SUA) correlates with arterial stiffness and inflammation markers in a cohort of women with systemic lupus erythematosus (SLE) without overt atherosclerotic cardiovascular diseases, who attended a community hospital. One hundred and two women with SLE were assessed as part of this cross-sectional study. Carotid-femoral pulse wave velocity (PWV) was measured using an automatic device (Complior). C-reactive protein (CRP), fibrinogen and homocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Much experimental and epidemiological evidence suggested that estrogen exert a vascular protective function and may have beneficial effects on endothelial function and atherosclerosis, raising the possibility of sex differences in arterial remodeling [37]. However, many studies indicated that SUA had greater influence on women [38, 39]. Recent studies showed a relationship between SUA and coronary atherosclerosis in women only [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Much experimental and epidemiological evidence suggested that estrogen exert a vascular protective function and may have beneficial effects on endothelial function and atherosclerosis, raising the possibility of sex differences in arterial remodeling [37]. However, many studies indicated that SUA had greater influence on women [38, 39]. Recent studies showed a relationship between SUA and coronary atherosclerosis in women only [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Kiani et al [55] showed that increasing age was independently associated with the progression of cIMT over a 2-year period, while Sabio et al [56][57][58][59][60] showed that increased PWV was associated with increased age. Salmon et al [18] showed that older age at diagnosis, longer duration of SLE, and higher homocysteine concentration are independently related to the progression of atherosclerosis in SLE.…”
Section: Agementioning
confidence: 97%
“…High levels of parathyroid hormone are related to renal osteodystrophy, a group of disorders that can be classified as osteitis fibrosa, osteomalacia, mixed uremic osteodystrophy and adynamic bone disease. Hyperuricemia is particularly common in patients with kidney disease, including Lesch-Nyhan, recent epidemiological studies suggest an independent association between asymptomatic hyperuricemia and increased risk of arterial hypertension, progression of CKD, cardiovascular events, and mortality [78,79]. Although short-term clinical studies support the beneficial effect of pharmaceutical reduction of serum uric acid on cardiovascular risk and renal disease progression, further randomized evidence will be required.…”
Section: Other Metabolic Complicationsmentioning
confidence: 98%